The Heidelberg Catechism: A 16th century quest for unity - Dreyer, Wim A. (HTS teologiese studies, 2014)
In this contribution the view is presented that the Heidelberg Catechism should be regarded as an attempt to promote unity between 16th century reformers and churches in the Palatinate. This, to some extent, determined the content of the Catechism resulting in some controversial issues receiving less attention. This in turn not only made the Catechism acceptable to a wide spectrum of Reformed Christianity, but also resulted in a creative and unique contribution to Reformed theology, almost a ‘third option’. It was soon used in different Reformed territories as a confession and acclaimed for its clarity in formulating the basic Reformed faith. Today the Heidelberg Catechism is regarded as one of the most ‘ecumenical’ documents of the 16th century. As such, it still promotes unity amongst many Reformed churches, including those in South Africa.